Hemireplacement Arthroplasty with Unipolar vs Bipolar Prosthesis for Displaced Hip Fractures in Elderly - Dutta, D; Bajracharya, AR (Journal of Nepal Health Research Council, 2010)
Background: Hip fractures are common occurrence in elderly with various methods of treatment practiced for its management. Hemireplacement with different types of prosthesis is most widely practiced, and cemented bipolar prosthesis being the current trend. The aim of this study is to compare the outcome of unipolar prosthesis which is the current practice at our hospital, with the bipolar prosthesis. Methods: This was a prospective study patients aged over 65 years with displaced femoral neck or trochanteric fracture underwent hemireplacement arthroplasty, cemented unipolar prosthesis was used in 18 patients and in 16 bipolar prosthesis was used. Functional outcome using Harris Hip Score and mobility score was compared between two groups. Results: The two groups of patients did not differ in their pre-injury characteristics (age, sex,fracture pattern, ASA grading, co-morbidity, mode of injury and pre-injury ambulatory status) and peri-operative parameters such as duration of operation, blood loss, hospital stay. One year after operation, there was no statistical difference in the functional parameters such as Harris Hip Score, mobility score and rate of complication in both the groups. Conclusions: Early results suggest that Cemented unipolar prosthesis are equally effective as compared to bipolar for the treatment of displaced hip fractures in elderly patients, in Nepalese context. Key words: hip fracture; hemiarthroplasty; harris hip score. DOI: 10.3126/jnhrc.v7i2.3022 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 131-134